Preference of specimen collection methods for human papillomavirus detection for cervical cancer screening: a cross-sectional study of high-risk women in Mombasa, Kenya - Griffins O. Manguro; Linnet N. Masese; Kishor Mandaliya; Susan M. Graham; R. Scott McClelland; Jennifer S. Smith (BMC, 2018)
Abstract Objectives Self-collection of genital specimens for high-risk types of human papillomavirus (hrHPV) detection may increase cervical cancer screening uptake. We hypothesized that women would prefer self-collection to clinician-collection of genital specimens. To test this hypothesis, and women's preference between two different self-collection approaches, a total of 199 women were enrolled in a cross-sectional study in Mombasa, Kenya. Materials and methods Participants provided self-collected specimens using the Evalyn cytobrush (Rovers) stored in a dry tube and the Viba cytobrush (Rovers) stored in wet Aptima media (Hologic). A clinician also collected cervical specimens for hrHPV testing and for cytology, and performed visual inspection using acetic acid. A post-examination questionnaire assessed preferences for the different methods of specimen collection. To test the difference in proportions for each collection method, we performed an exact binomial probability test, under the null hypothesis that women would prefer each specimen-collection method equally. Results Most women preferred clinician-collection over self-collection (68% versus 32%, p < 0.01). For self-collection, dry-self collection with the Evalyn brush was preferred over the wet-selection with the Viba brush (53% versus 27%, p < 0.01). There was no association between preference for self-collection and preference for a particular self-collection cytobrush. Conclusion Further research to understand and address obstacles to self-collection of genital specimens may be needed to improve the uptake of self-collection for cervical cancer screening, especially in settings with poor access to trained healthcare providers.